2003
DOI: 10.2337/diabetes.52.1.187
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Gene Variable Number Tandem Repeat Class I/III Polymorphism Is in Linkage Disequilibrium With Birth Weight but Not Type 2 Diabetes in the Pima Population

Abstract: The insulin gene variable number tandem repeat (INS-VNTR) is proposed to exert pleiotropic genetic effects on birth weight and diabetes susceptibility. In our study, we examined the influence of a polymorphism in tight linkage disequilibrium with INS-VNTR (؊23Hph1) on birth weight and type 2 diabetes in the Pima population. A parent-offspring "trio" design was used to assess parent-of-origin effects and population stratification. The presence of the -23Hph1 T-allele was associated with lower birth weight (n ‫؍… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 31 publications
6
51
2
Order By: Relevance
“…In fact, the positive association is derived solely from a single study showing a strong association [21], whereas the remaining studies do not show significant associations between the class III/III genotype of the INS-VNTR and Type 2 diabetes. Furthermore, other studies have also examined a potential association between Type 2 diabetes and the class III allele, and even though one did report an association between Type 2 diabetes and paternally inherited class III alleles [10], these studies reported a lack of overall association between the INS-VNTR class III allele and Type 2 diabetes [10,13]. The genotype distribution among the Type 2 diabetic patients in the six studies from the meta-analysis was very different.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In fact, the positive association is derived solely from a single study showing a strong association [21], whereas the remaining studies do not show significant associations between the class III/III genotype of the INS-VNTR and Type 2 diabetes. Furthermore, other studies have also examined a potential association between Type 2 diabetes and the class III allele, and even though one did report an association between Type 2 diabetes and paternally inherited class III alleles [10], these studies reported a lack of overall association between the INS-VNTR class III allele and Type 2 diabetes [10,13]. The genotype distribution among the Type 2 diabetic patients in the six studies from the meta-analysis was very different.…”
Section: Discussionmentioning
confidence: 93%
“…Concerning Type 2 diabetes, it was reported from a study examining 155 parent-offspring trios that the association between Type 2 diabetes and the INS-VNTR is mediated exclusively through the paternally transmitted class III allele [10]. However, the impact of imprinting on the INS-VNTR in relation to Type 2 diabetes has not yet been clarified, as a study of Pima Indians, also using parentoffspring trios, failed to demonstrate a clear parentof-origin effect on risk of Type 2 diabetes [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors are likely to be involved. In particular, genetic factors are thought to influence fetal growth [12,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%